The phylogenetic landscape and nosocomial spread of the multidrug-resistant opportunist Stenotrophomonas maltophilia - Matthias I. Gröschel (Nature Portfolio, 2020)
Multidrug resistance of the opportunistic pathogen Stenotrophomonas maltophilia is an increasing problem. Here, analyzing strains from 22 countries, the authors show that the S. maltophilia complex is divided into 23 monophyletic lineages and find evidence for intra-hospital transmission.